$2.30 African and the $2.20 EU cow - Abd Razak, Dzulkifli (2008)
I AM of the opinion that it I would be an injustice if we A were to completely extract and enjoy the benefits without leaving anything at all for future generations." Such were the profound words of concern voiced by the Yang diPertuan Agong on the occasion of his birthday last week. He further acknowledged that "if necessary, the people should change their lifestyle to help reduce the impact of the rise in prices on them". These suggestions cannot come at a better time, and it applies not only to Malaysia but more so to the international community. The reminder is all the more appropriate as we try to embrace the idea of "sustainable development" as the new thrust of thinking for our own survival on planet Earth.